Effects of Drug Resistance on the Global Spread of Malaria: A Systematic Literature Review - Ashenafi Woldemichael Woime (Health Science Reports, 2026)
ABSTRACT Background and Aims Malaria remains a major health crisis in tropical regions, with Sub‐Saharan Africa bearing the heaviest burden. While insecticide‐treated nets and artemisinin‐based combination therapies (ACTs) have reduced cases, emerging parasite resistance to artemisinin threatens these gains. This review synthesizes evidence on how drug resistance impacts malaria transmission and control globally. Methods This systematic review followed PRISMA 2020 guidelines and was registered with PROSPERO (CRD420261336060). A comprehensive search of PubMed/MEDLINE, Embase, and Web of Science, supplemented by hand‐searching and grey literature, identified studies published between January 2011 and December 2025. Of 897,299 initial records, 22 studies met the inclusion criteria after screening and quality assessment using JBI, the Newcastle–Ottawa Scale, and Cochrane RoB 2 tools. Data were summarized thematically; meta‐analysis was not conducted due to heterogeneity and varying bias. Sensitivity analysis confirmed robustness. Results Drug resistance reduces treatment effectiveness and increases transmission. Artemisinin resistance, primarily associated with kelch13 mutations, is established in Southeast Asia (prevalence: 5%–47%; 95% CI: 32%–41%) and emerging in Sub‐Saharan Africa and South Asia. Resistance to partner drugs and older antimalarials remains widespread. Resistant strains increase treatment failure from 5% to 15%–20%, prolong infections, and enhance gametocyte carriage by 2–3‐fold and mosquito infection rates. Conclusion Without urgent global collaboration, resistance will undermine malaria elimination and increase disease burden. This review calls attention to novel treatments, enhanced surveillance, and regionally tailored strategies to contain resistance and sustain malaria control efforts worldwide.